Nonlinear elasticity in buildings: a prospective way to monitor structural health. (2017) - Astorga, Ariana; Guéguen, Philippe; Kashima, Toshihide
Abstract: Nonlinear elasticity has been observed in different materials and at different scales (from laboratory tests to the crust of the Earth). This behavior is evidenced by nonlinear response accompanied by slow dynamics, a process in which elastic properties recover (fully or partially) values previous to the excitation. In this study we show that nonlinear elasticity also occurs at buildings scale, where nonlinear signatures can be observed even for low levels of strain, and slow dynamics is seen at both short and long-term monitoring. Although the physics behind this response remains unknown, it is believed that this fascinating behavior is controlled by the presence of cracks, heterogeneities and dislocations; and therefore, it might be linked to the level of structural damage. By using data from Japan, we analyze the dynamic response of 24 buildings facing strong motions. The objective is to monitor variations of fundamental frequency over time and correlate them with different levels of structural drift and loading. Analyzing nonlinear elastic behavior might become a very useful and valuable way to monitor the time evolution of structural health, and hopefully, a predictive method to estimate deterioration and likely structural damage over time.